Optimization of Nanoemulsion Formulation from the Aqueous Fraction of Dayak Onion (Eleutherine bulbosa (Mill.) Urb) Tuber Extract Using Variations of Olive Oil, Tween 20, and PEG 400 - Husnul Warnida; Umi Erabiatul Azira; Supomo Supomo; Rizqa Akhriana Putri; Eka Siswanto Syamsul (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2026)
Dayak onion (Eleutherine bulbosa (Mill.) Urb) is known for its antioxidant, anti-inflammatory, and antimicrobial activities, attributed to its flavonoid, alkaloid, and saponin contents. However, the bioavailability of these active compounds is limited due to poor stability and absorption. To enhance their effectiveness, nanoemulsion formulations were developed. This study aimed to investigate the effects of varying concentrations of olive oil, Tween 20, and PEG 400 on the physical characteristics of nanoemulsions containing the water fraction of Dayak onion bulb extract, and the optimization was performed using a D optimal mixture design (Design Expert 13) with three independent variables: olive oil (1–11%), Tween 20 (1–11%), and PEG 400 (1–16%). The extract concentration was kept constant at 1%. The responses evaluated were pH, creaming index, transmittance, droplet size, polydispersity index, and zeta potential. The optimum formula was selected based on the highest desirability value. The optimal formulation exhibited a stable pH (5.00–6.12), a low creaming index (0–0.3), an average particle size of 308 nm with a polydispersity index of 0.51, and a zeta potential of –38.6 mV, indicating good electrostatic stability. However, the transmittance percentage did not reach the ideal standard (>80%). Significant differences were observed between predicted and experimental values for the creaming index and transmittance, and changes in the creaming index occurred during 30 days of storage. Further optimization is recommended to enhance the stability and clarity of the nanoemulsion.